2012
DOI: 10.1002/ppap.201200076
|View full text |Cite
|
Sign up to set email alerts
|

Feeding‐Gas Effects of Plasma Jets on Escherichia coli in Physiological Solutions

Abstract: The effects of air and N2 plasma jets on Escherichia coli inside four different physiological solutions and deionized water are reported here. The feeding gases are found to influence the plasma compositions, the interactions with the liquids, and the subsequent bactericidal effects depending on the aqueous solutions to which they are exposed. Air plasma enhances the bactericidal effects of deionized water and saline by acidification. On the other hand, N2 plasma induces higher toxicity in phosphate buffered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…However, environmental influences have not been frequently reported. A recent study demonstrated that the bactericidal effects of plasma in water and saline increase due to the acidification of solutions by air plasma and that PBS exposed to N 2 plasma becomes highly toxic to bacteria [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, environmental influences have not been frequently reported. A recent study demonstrated that the bactericidal effects of plasma in water and saline increase due to the acidification of solutions by air plasma and that PBS exposed to N 2 plasma becomes highly toxic to bacteria [18].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma can produce different control outcomes to the same microbial species, depending on the surrounding environment. One study demonstrated that bacteria present in various physiological fluids are killed by plasma at different rates and that the different death rates are probably caused by differential changes in components and ions in the solutions caused by plasma [18]. In addition, plasma is more effective in eradicating bacteria on non-biological surfaces than on skin [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that the formation of DNA strand breaks resuspended in buffer such as phosphate buffered saline (PBS) or Tris-EDTA (TE) is significantly reduced compared to that in water (Leduc et al 2009;O'Connell et al 2011). There was almost no DNA damage after plasma treatment in culture media probably because radical/electron scavengers are enriched in the media and plasma-induced acidification of the media is much less than that of PBS or water (Leduc et al 2009;Baik et al 2013). However, even when dried DNA isolated from cells is exposed directly to plasma treatment, in order to exclude any contribution of surrounding environmental factors such as buffer and culture media, DNA strand breaks and degradation occur very rapidly suggesting that factors other than the chemical components of plasma might affect on DNA stability ( Fig.…”
Section: Plasma Might Induce Ros-dependent Apoptosis and Dna Damage Smentioning
confidence: 92%
“…1). Although the physical and chemical properties of plasma jet vary considerably according to the configurations of plasma sources, input power, type of feeding gas, and the aqueous environment to which the cells are exposed, there is no doubt that plasma used for medical therapy creates a large amount of ROS/RNS as its major compositions and that these influence the physiological milieu of cells and tissues (Graves 2012;Baik et al 2013). When present at low levels, ROS/RNS play an important role as regulatory mediators in various physiological signaling processes such as cell proliferation, migration, and vascular relaxation, whereas at high concentrations they are implicated in serious oxidative stress leading to the pathogenesis of cancer, diabetes, atherosclerosis, and neurodegenerative diseases as well as senescence (Dröge 2002).…”
Section: Extracellular and Intracellular Ros/rns-induced Apoptosis Bymentioning
confidence: 99%